A musealização do património imaterial da Escola Portuguesa de Arte Equestre - Ribeiro, Catarina Chaves, 1994- (2018)
This dissertation deals with theoretical issues related to intangible heritage and its preservation, communication and exhibition in museums. The selected cases of study were the Portuguese School of Equestrian Art and the Lusitanian horse. In order to achieve this objective, this work begins with a reflection on what intangible heritage is, the evolution of the concept over time and the problems inherent in its inventorying. Then a connection is made to the world of museums and the main problems of the musealization of this type of memories are studied. The second part of the work seeks to develop the history of the relationship between man and horse, the origins of the lusitano horse and the Portuguese traditions related to horse riding until the contemporary manifestations of Portuguese equestrian art are reached. Next, a chapter is dedicated to the Portuguese School of Equestrian Art, taking into account their origins and traditions, the exercises that characterize the High School are presented and their equipment and spaces are mentioned, trying to justify the international framework that his candidacy for UNESCO's Intangible Heritage symbolizes. In order to realize these ideas, it is proposed the creation of traveling exhibition room, where the use of new technologies is inevitable. This space follows an exhibition model that can be adapted to different contexts, to be able to follow the national and international exhibitions of the Portuguese School of Equestrian Art